Planejamento governamental : aspectos teoricos e uma analise das experiencias mundial, brasileira e cearense - Barbosa, Arnoldo Parente Leite (1986)
Planning always fascinates and dazzles mankind since his earIiest age, when man researched to see the future, which is unknown and mysterious to him. One of the characteristics of the human being is to make plans, and this activity is inherent to man and also to the societies. The brazilian Iiterature available about this theme developes into two great lines, almost always without a unit, producing in one side theorical studies, and in the other, analysis of specifcs experiences of some countries, regions and states in some given period of time. This master dissertation presented at EBAP/FGV, named 'Gouvernmental Planning.Theorical views and an analysis of the world, brasilian and cearense experiences', holds in a unique study the theorical and praticaI vie~s within a logical and .didatic exposure with the objective of reviewing and clarifying the subject and wants to be bibliographical material to graduate and post-graduate courses of Governmental Planning. For a better comprehension of the experiences of planning it presents originaly the theorical aspects, defining the subject and relating its functions and characteristics. This work shows the relation of planning with power and politics including the discussion about neutrality and racionality, as well as its use as an instrument of power. It also shows planning as a process with definition and the description of the three theorical models - Bromley, Tristão It presents the difficult problem of liberty in the private sector comparing it -with governmental intervention, since its first expressions in the URSS, after the revolution of october 1917, showing the European and the United States of America experiences, and the one of undevelopped countries, each one with its historical conditions and institutional peculiarities. It analyses the world and brazilian experiences(divided into phases: occasional - until 1930, experimental - 1930-1964 and scientific - 1964-1986), and it synthesizes the last one based on the points of visw of various authors that have been examined particulary Benedicto Silva, Werner Baer, Issac Kerste netzky, 'Annibal V. Villela, Jorge Vianna'Monteiro and Luiz Rober to Azevedo Cunha. In the case of Ceará ( 1963-1986 ), a factual description of plans has a time sequence ( as an example of the brazilian plans ), a simple didactic form looking for a better comprehension of the subject was chosen. At the same time, it analyses the plans in its economic, social, political and cultural sides, integrating them and trying to mesure the history of state planning in its totality. The traditional view comparing proposed objectives attained very commum in the analyses of planning experiences, is not studied in a stricto-sensu. In the other side, it emphasizes the aspect which we judge more important:the identification of the evolution of the arrangements because planning appears on them and its feasibility depends particulary on the institutional contexto Exempting the concept of planning from the delit of its failure to attain the greater. part of its objectives, the work points to a series of disadvantageous factors that underlines a crisis sltuation: apologetical and triumphal objectives innocuous rhetorici the use of planning to fortify and to make feasible the interess of the domiriánt classi excessiveness of the techniques and thesis of neutrality of planning to obtain power; manipula.tion of planning as an instrument of mystification, as well as its use as a talisman and a way to enter politics ( specialy in Ceara ); the elimination o f the federal character of the states with the tributary system, leading to a centralization of the decision-making ( and the power ) i absence of continuity in the economic policies in the long term and consequently an adminlstrative discontinuance and, at last, the real nature of planning praticed in Brazil and Ceará, which, being indivative, does not hold the control of all the variables of the processo The appearance of a new paradigma for gouvernnerntal planning would pass necessarily through the antithesis of the difficulties pointed out in this study